Identification of Lasiodiplodia species causing brown leaf spot disease of cassava in Ghana - Abdulai, Muntala; Ankomah-Boamah, Frank; Adomako, Joseph; Utku, Yükselbaba; Gyasi Santo, Kwadwo; Asomah, Shadrack; Armooh, Bernard (Agriculture and Natural Resources, 2026)
Importance of the work: This research connected Lasiodiplodia species to brown leaf spot (BLS) disease of cassava in Ghana, since there is a lack of published data regarding Lasiodiplodia theobromae (Pat.) Griffon & Maubl., Lasiodiplodia mediterranea Linald., Deidda & Berraf-Tebbal and Lasiodiplodia pseudotheobromae A.J.L. Phillips, A. Alves & Crous, as causative agents of BLS disease in cassava in Ghana. Objectives: To isolate, identify and describe the fungal pathogens that cause cassava BLS in Ghana. Materials and Methods: Diseased cassava leaves with BLS symptoms were collected from farms in five communities, selected from Sunyani Municipality, Sunyani West Municipality and Dormaa East District, Ghana. Morphological (conidial size and shape, colony diameter, colony growth rate) characterization was applied in identifying Lasiodiplodia spp. to the genus level, while a multi-locus study of the internal transcribed spacer (ITS) and β-tubulin (TUB2) regions was used to identify these pathogens to the species level. Results: The fungal pathogens L. theobromae, L. mediterranea and L. pseudotheobromae were identified morphologically and molecularly using their ITS and TUB2 sequences. Together, these three isolates produced the characteristic BLS symptoms that were seen in farmers’ fields. Conidia widths were not significantly different, except for the Nsoa community (5.477 µm). The conidia lengths of the Asua (35.05µm), Asuo (73.90 µm), Kyere (46.20 µm), Nsoa (37.43 µm) and Wam (48.78 µm) communities were not significantly different, while the D.A (38.22 µm), K.B (36.45 µm), Yaw (27.67 µm) and Akon (39.38 µm) communities were significantly different from Asuo (73.90 µm). For both the colony diameter and average mycelial growth rate, all communities were community were significantly (p < 0.001) different, except for Nsoa (21.1mm, 2.7 mm/day). Pathogenicity testing on healthy plants produced similar symptoms, validating Koch’s postulates. Main finding: The present study was the first of its kind implicating L. theobromae, L. mediterranea and L. pseudotheobromae as causal agents of BLS on cassava in Ghana.